The Rule of Disposal of the Matrimonial Property - Meladze, Giorgi (Journal of Law, 2021)
Legal norms governing relations between spouses are considered to be the acquisition of civilized states from ancient times. Numerous principles and regimes have been developed in the modern legal systems of the world in order to regulate the property relations of spouses. Accordingly, for Georgian family law, as one of the young systems, it is necessary to study the relevant experience of the states with leading jurisdictions through the use of the comparative legal method. Also, the decisions made in the Georgian court practice in this direction requires critical understanding, identification of problems, and development of ways to solve them. The study aims to present and solve the problematic issues of spouses' co-ownership disposition based on the above-mentioned legal sources.